Enhanced recovery programmes: Do these have a role in gynaecology?. (August 2013) - Bell, A.; Relph, S.; Sivashanmugarajan, V.; Yoong, W.
Abstract : Enhanced recovery (ER) has become increasingly ubiquitous in most surgical specialities and its use is gathering pace. It has been proven to be a safe and effective means of managing patients perioperatively, while also improving patient outcomes, and its use in gynaecology has recently been supported by the Royal College of Obstetricians and Gynaecologists (RCOG). ER is gaining popularity, despite being a diversion from the traditional surgical approach, demanding an orchestration of primary, secondary, social and auxillary care teams to work effectively. ER has been heralded as improving clinical outcomes and patient satisfaction, while simultaneously allowing increased patient turnover. This has potentially massive impacts on service provision within the NHS and is likely to become a proof of concept that the NHS can adapt. ER can be championed as a flexible and contemporary healthcare model, which can be improved as patients' needs and NHS resources change.